DESAIN E-MODUL BERBASIS KONTEKSTUAL TERINTEGRASI NILAI-NILAI KEISLAMAN PADA MATERI LAJU REAKSI - Badi'atul Masngudah; Nurfina Aznam (Jurnal Riset Pendidikan Kimia (JRPK), 2025)
The increase in juvenile delinquency can be overcome by character education that combines Islamic religion and science. In addition, contextual learning is a solution to overcome students' difficulties in learning the material of reaction rates. This study aims to determine the characteristics, analyze the feasibility, usability, and determine students' responses to the developed e-module. This study uses the DBR (Design-Based Research) development model which consists of three stages: analysis and exploration, design and construction, and evaluation and reflection. This study involved experts (chemistry, Islamic religion, and media), chemistry teachers of MA in DIY, and students in phase F. The instruments used were validation sheets and questionnaires. Data analysis used qualitative descriptive for qualitative data and descriptive statistics for quantitative data. The results of the study indicate that the required characteristics of the e-module are that the teaching materials are made electronically and are easily accessible, contain images/illustrations about the material, contain the context of the material integrated with Islamic values and related to daily life, and are presented in the form of a flipbook. Based on expert assessments, the developed e-module is considered feasible with revision. According to the teachers' assessment, the developed e-module fell into the very good category, achieving an average score of 98 and a 91% ideality percentage. Meanwhile, student responses based on the readability test yielded an average score of 68, falling into the very good category with an 85% ideality percentage.